2017
DOI: 10.1037/pag0000186
|View full text |Cite
|
Sign up to set email alerts
|

In the eye of the beholder: Can counter-stereotypes change perceptions of older adults’ social status?

Abstract: Negative age-related stereotypes often entail the perception that older adults have a lower social status than middle-aged adults. We hypothesized that older adults are perceived to have lower social status because they are less likely to be seen in prestigious occupational positions. People tend to infer general assumptions about group characteristics from exemplars. According to this, presenting a stereotype-inconsistent exemplar (i.e., older person in a high-status position) should change perceptions of old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 50 publications
(78 reference statements)
2
26
0
Order By: Relevance
“…Consistent with previous research [11, 12, 31], study 2 found an inverted U-curve shape in perceived social status across the lifespan. However, we also observed an interesting bimodal distribution for one of the measures indicating that there may be one group of participants who viewed older adults as having high social status and another who view them as having low social status.…”
Section: Discussion Studysupporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with previous research [11, 12, 31], study 2 found an inverted U-curve shape in perceived social status across the lifespan. However, we also observed an interesting bimodal distribution for one of the measures indicating that there may be one group of participants who viewed older adults as having high social status and another who view them as having low social status.…”
Section: Discussion Studysupporting
confidence: 80%
“…In line with previous research [11, 12, 31], we submit that older adults are likely to share the general perception of an inverted U-curve shaped function of age-related social status across the life span, but do not share this view for themselves. Thus, although they may perceive that older adults as a group have low social status, they will perceive themselves as individuals as having a relatively higher social status than older adults in general.…”
Section: Self- and Other Perceptions Of Social Status: Status Ambivalsupporting
confidence: 68%
See 1 more Smart Citation
“…The resulting increase in energy and social resources available for reproduction could help explain the increased production of costlier sons observed during mothers' mid‐reproductive careers. In many traditional, natural fertility societies, women's aging is often associated not only with somatic maturation but also with increases in social status and experience (McDonald & Mair, ; Robertson & Weiss, ). Social status and experience can, in turn, facilitate access to higher quantities and quality of food resources (Meehan, Quinlan, & Malcom, ) and reduced energy expenditures.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the broad dispersion of negative stereotypes towards older workers, empirical research on their impact on performance is still incipient. As indicated by Chiesa et al [5], the loss in productive terms seems to be mediated by the self-efficacy of the group of older workers, which offers an opportunity to mitigate reduced performance through an intervention to increase self-efficacy [34]. Self-efficacy consists of the personal beliefs in their own abilities to implement everything needed to perform a specific task in a satisfactory way [35,36].…”
Section: Introductionmentioning
confidence: 99%